Adaptive Learning Technologies for Inclusive Education: Enhancing Social Development through Personalized Digital Ecosystems (International Journal of Scientific Research in Science and Technology, 2024)
Adaptive learning technologies, powered by data analytics and artificial intelligence, offer a promising avenue for fostering inclusive education by tailoring learning experiences to individual needs. This article explores the potential of personalised digital ecosystems to enhance social development among learners. By leveraging real-time data on learners’ progress, engagement, and preferences, these ecosystems can create collaborative learning opportunities, promote empathy and understanding, and address the diverse needs of learners. Additionally, adaptive learning technologies can facilitate the development of essential social skills, such as communication, problem-solving, and teamwork. Through personalised feedback, adaptive learning technologies can help learners identify their strengths and weaknesses, fostering a sense of self-awareness and confidence. In addition, by providing opportunities for peer interaction and collaboration, these technologies can cultivate empathy, understanding, and respect for diverse perspectives. This paper explores the design implementation strategies for developing adaptive learning technologies that effectively support social interaction, foster a sense of belonging, and contribute to a more equitable and inclusive educational landscape.